A study on nutritional status of preschool children and knowledge with special references to breastfeeding practice in urban area - Birajdar, Shrikant S.; C. S., Jayalekshmi; Jadhav, Bhimrao S.; Nagaonkar, Ajit S. (International Journal Of Community Medicine And Public Health, 2024)
Background: The nutritional status of preschool children is a critical indicator of their overall health and development. Breastfeeding provides best start of life to babies as well as improves the health of mothers and babies. Objectives were to assess the nutritional status of preschool children and to Investigate the impact of breastfeeding practices on children’s nutritional outcomes and breastfeeding practices of their mothers. Methods: This cross-sectional study was conducted in an urban slum area and involved a sample of preschool children aged 3 to 6 years. Complete enumeration of children of 3-6 years age group was done. Nutritional status was assessed through anthropometric measurements, including height, weight and mid upper arm circumference. Data on breastfeeding practices were collected through structured interviews. Data was analysed using MS excel and chi-square statistical tests was applied. Results: There were 334 study participants of which 7.5% had stunting and 62.87% were underweight. It was found that 18.56% had history of low birth weight. 90.12% were exclusively breastfed and breastfeeding was continued up to 2 years for 28.14% and more than 2 years for 71.86% children. It was also found that history of low birth weight of children is significantly associated with malnourishment (p≤0.05). Conclusions: The study revealed that a substantial proportion of preschool children in the urban area were experiencing malnutrition. The breastfeeding practices were fair among the mothers of the children. Targeted education and awareness programs to enhance the nutrition can improve the overall health of preschool children in the urban setting.